2004
DOI: 10.1111/j.1745-459x.2004.tb00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Scaling Errors

Abstract: Judges were required to rate the total intensity of NaCl solutions using a variety of unstructured category and line scales under a ‘rank‐rating’ protocol and a traditional protocol that did not allow retasting or the reviewing of scores. The various scales and protocols induced two types of scaling errors. The first type was named a different‐stimulus error. This involved a judge rating a stronger stimulus as equal to or less than a weaker stimulus. The second type was named a same‐stimulus error. This involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 22 publications
3
23
1
Order By: Relevance
“…In previous studies, unlike this study, rank-rating showed better performance than monadic rating for intensity evaluations based on different stimulus error rates and discrimination abilities (10,13,16,17). The occurrence of errors during sensory evaluation is largely due to sensory adaptation and forgetting the taste intensity of previously tasted samples (13).…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…In previous studies, unlike this study, rank-rating showed better performance than monadic rating for intensity evaluations based on different stimulus error rates and discrimination abilities (10,13,16,17). The occurrence of errors during sensory evaluation is largely due to sensory adaptation and forgetting the taste intensity of previously tasted samples (13).…”
Section: Resultscontrasting
confidence: 63%
“…The error rate for a wrong ranking order was calculated for ranking and rating data. The error rate for a wrong ranking order refers to the rate of different-stimulus errors where a lower or equal score is given to a stronger stimulus (10). A significance level of p<0.05 was used.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies confirmed this Kim & O'Mahony, 1998). Park et al (2004) designed an experiment, using both Rank-Rating and a more traditional protocol, to test both of Jeon et al's hypotheses by examining 'different-stimulus' and 'same-stimulus' scaling errors. They noted that different-stimulus scaling errors occurred more often for a category scale with fewer categories.…”
Section: Introductionmentioning
confidence: 75%
“…Jeon, O'Mahony, and Kim (2004) noted that the inappropriate assignment of scores could fall into two types, while Park, Jeon, O'Mahony, and Kim (2004) later gave them names. What they called 'same-stimulus' errors, involved giving perceptually 'identical' stimuli different scores.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation